Nothing gets wasted - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A new fuel for cooking and heating, which at FCFA 50/kg is cheaper than firewood, is coming onto the market in Burkina Faso. Briquettes of compressed agricultural waste (straw and cotton stems) are shaped into cylinders 7cm in diameter; they are...